Video data for "Challenges in Classifying Cavitation: Correlating High-Speed Optical Imaging and Passive Acoustic Mapping of Cavitation Dynamics" - Wu, Q; Gray, M; Smith, C A B; Bau, L; Cleveland, R O; Coussios, C; Stride, E (University of Oxford, 2024)
High speed camera video footage supporting the above publication